2022
DOI: 10.1155/2022/2698869
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BRINP3 Predicts Poor Prognosis and Promotes Cancer Cell Proliferation and Migration via MAP4 in Osteosarcoma

Abstract: Osteosarcoma (OS) is a primary malignant bone tumor most commonly affecting children and adolescents and is characterized by loss of differentiation. Bone morphogenetic protein/retinoic acid inducible neural-specific 3 (BRINP3) has been reported to regulate the differentiation of osteoblasts. However, the role that BRINP3 plays in the progression of osteosarcoma remains unknown. We found in this study that BRINP3 was highly expressed in 64.13% of human osteosarcoma tissues and it was associated with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In the present trial, we profiled the somatic mutations from baseline blood samples of the enrolled patients and explored potential predictive biomarkers for treatment with short-course chemotherapy combined with sintilimab as per our predefined exploratory endpoints. We discovered that patients harboring any of the BRCA2, BRINP3, FBXW7, KIT or RB1 abnormalities had worse clinical outcomes, with median PFS becoming definitely shorter than those without abnormalities, findings also reported in previous studies [29][30][31][32][33] . Several studies have demonstrated a proven correlation between ctDNA clearance and clinical outcomes for a variety of tumor types [34][35][36] , and PB ctDNA analyses of certain mutations have been proposed as surrogates for advanced lung cancer biopsy samples 37 .…”
Section: Discussionsupporting
confidence: 85%
“…In the present trial, we profiled the somatic mutations from baseline blood samples of the enrolled patients and explored potential predictive biomarkers for treatment with short-course chemotherapy combined with sintilimab as per our predefined exploratory endpoints. We discovered that patients harboring any of the BRCA2, BRINP3, FBXW7, KIT or RB1 abnormalities had worse clinical outcomes, with median PFS becoming definitely shorter than those without abnormalities, findings also reported in previous studies [29][30][31][32][33] . Several studies have demonstrated a proven correlation between ctDNA clearance and clinical outcomes for a variety of tumor types [34][35][36] , and PB ctDNA analyses of certain mutations have been proposed as surrogates for advanced lung cancer biopsy samples 37 .…”
Section: Discussionsupporting
confidence: 85%
“…HOTAIR also is increasingly recognized as a critical contributor in the metastatic process for a number of cancers more broadly, specifically due to its role as a regulator of epithelial cell plasticity and the epithelial-to-mesenchymal transition (EMT) 67 , although our GSVA analyses did not identify major differences in gene expression in the EMT or other hallmark pathways overall. Much less is known about the function of BRINP3, a developmental gene whose reduced expression in cLNM was the second strongest DEG in our analysis, though it has been implicated as a cell cycle regulator and associated with cellular proliferation and migration in osteosarcoma 68 . Intriguingly, two other genes (DLX1, LMX1B) that also had lower expression in the cLNM are homeobox genes 69 , suggesting the potential importance of dysregulation of developmental and differentiation processes in PTC cLNM.…”
Section: Discussionmentioning
confidence: 93%
“…It was also found that mesenchymal lung cancer cells exhibited higher levels of radioresistance than cancer cells of the epithelial phenotype (Yang and Weinberg 2008 ). More importantly, it was also observed that radiotherapy might induce EMT in vivo, as demonstrated by comparing surgically resected NSCLC specimens before and after radiotherapy (Zeng et al 2022 ). More evidence suggests that IR-induced EMT accelerates the malignant features of radiotherapy-treated tumours, leading to recurrence and treatment failure of nasopharyngeal, breast, oesophageal, hypopharyngeal, and lung cancers by promoting invasion, migration, radiation resistance, and chemotherapy resistance (Li et al 2020 ; Zeng et al 2022 ; Zhang et al 2016 ; Zhang et al 2019a ; Zhang et al 2019b ; Zhang et al 2019c ).…”
Section: Discussionmentioning
confidence: 98%